Designing a Financial Resource Allocation Model Using Goal Programming Approach: A Case Study of a Hospital in Iran - Marzieh Lashkari; Vahid Yazdi-Feyzabadi; Mohsen Mohammadi; Hossein Saberi; Mohammad Hossein Mehrolhassani (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Prioritization and resource allocation are the most important processes in managing and developing each organization. Given the high turnover and cost of hospitals in health system, this study aimed to provide a model for financial resource allocation with the Goal Programming (GP) in Afzalipour teaching medical center in Kerman. Methods: This mixed method and case-study study was conducted in Afzalipour teaching medical center located in Kerman, south-eastern of Iran. Participating key informants and operation research experts, twelve focus group discussions (FGDs) were developed to extract a goal programming model. Then, the hospital accounting data were collected from 2010- 2013 according to the extracted model. The WinQSB software was used for running the model. Results: The findings of this study showed that the share of personnel costs of this hospital was 72% which 28% was devoted to fee-for-service (FFS) and contractual services, current and other costs were 6%, 2%, and 12%, respectively. However, the findings of goal programming model showed that the optimum and satisfactory amount of personnel costs must be 66%, 14% of which were allocated to the FFS cost. The share of contractual services, current and other costs must be 15%, 2%, and 17%, respectively. Conclusion: The results showed that resource allocation in the hospital follow merely the accounting perspective rather than optimum and satisfactory ones. It is suggested in order to achieve the optimum values, the board of trustees should be institutionalized in practice; moreover, the outsourcing services should be addressed more. Therefore, personal costs which include a large part of costs can be reduced.